Teacher Professionalism in Learning in Madrasah Ibtidaiyah Muhammadiyah Tegalurung Balongan Indramayu - Widiya Lestari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
In the world of education, the teacher is an educator, mentor, trainer, and curriculum developer who can create conditions and a conducive learning atmosphere, namely a fun, interesting, and not boring learning atmosphere. A professional teacher is a determining factor for a quality education process. The purpose of this study is first to determine the professionalism of teachers in learning at MI Muhammadiyah Tegalurung. Second, to determine the quality of teachers in developing learning at MI Muhammadiyah Tegalurung. As for the data collection method that the authors use in this study is a descriptive qualitative method in its elaboration in the form of; interview, observation, and documentation. And the object of research is the teacher and head of the madrasa at MI Muhammadiyah Tegalurung. The results of the study show that in the development of teacher professionalism in learning at MI Muhammadiyah Tegalurung are (1) the professionalism of teachers in learning at MI Muhammadiyah Tegalurung is that there are 2 programs that have been implemented, namely the certification program and the supervision program. The certification program at MI Muhammadiyah Tegalurung has been well implemented, and the supervision program has also been optimal. (2) The quality of teacher professionalism in learning development at MI Muhammadiyah Tegalurung is stated to be of quality as evidenced by documentation data from madrasas and interview results regarding the teaching and learning process at the madrasah.